PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN UD AGRO ALAM RAYA Dsn. Gambyok, Ds. Sidoharjo, Kec. Tanjunganom, Kab. Nganjuk - Rikka, Mardiana; Yanda Bara, Kusuma (Jurnal Bisnis Indonesia, 2021)
To achieve organizational goals, one of the things that managers need to do is to improve leadership and provide the driving force that results in,channeling, and maintaining employee behavior to be willing to work inaccordance with what the organization wants. The driving force is the motivationand discipline of work for employees. The problem raised in this study is the lackof clarity in making decisions and the lack of motivation and work disciplinegiven by the company to employees. This study aims to determine the effect ofleadership, motivation and work discipline on the Employee performance of UD.Agro Alam Raya in Nganjuk. This research uses descriptive research and quantitative approach. Thepopulation in the study was 50 employees of UD. Agro Alam Raya in Nganjuk.The sampling technique used is saturated sampling technique so that the samplingtechnique by taking all members of the population as respondents. Data iscollected by questionnaire which has been tested for validity and reliability. Thedata analysis technique used is multiple linear regression. Based on data analysis, it can be concluded that there is a simultaneousand partial influence between the variables of Leadership, Motivation and WorkDiscipline on Employee Performance UD. Agro Alam Raya in Nganjuk Keywords: Leadership, Motivation, Work Discipline and EmployeePerformance DOI : ttps://doi.org/10.33005/jbi.v12i1.2602